IMPLEMENTATION OF SIMPLE ADDITIVE WEIGHTING (SAW) METHOD FOR DESIGN AND BUILD DECISION SUPPORT SYSTEM OF LAPTOP SELECTION (Case Study: IT Store) - Hariyanto Setiadi, Gregorius; Adline Twince Tobing, Fenina; Nainggolan, Rena (International Journal Science and Technology, 2023)
Laptop is a small computer that is easy to carry anywhere, which makes everyone want to have one because of its convenience. However, the laptops currently available have various specifications, so users feel confused about choosing and buying the laptop they want. Therefore, this research was conducted to build a web-based decision-support system. The method used in this decision support system is simple additive weighting as a criterion for calculating laptop recommendations. The SAW method is a weighted addition method to determine the weighted sum to determine ranking. User satisfaction test results using a questionnaire using the End User Computing Satisfaction (EUCS) method The results of the calculation of the user satisfaction test obtained a result of 85.66%, which means that the system built can be useful for users in providing laptop recommendations.